2020
DOI: 10.2147/oaem.s241124
|View full text |Cite
|
Sign up to set email alerts
|

<p>Brain CT Findings in Patients with First-Onset Seizure Visiting the Emergency Department in Mashhad, Iran</p>

Abstract: Introduction: Regarding the complications and costs of CT imaging for patients, this study aimed at investigating the necessity of CT scans in patients visiting the emergency unit with first-onset seizure. Methods: One hundred patients who had experienced their first seizure were enrolled. Their CT scan was studied, and based on the radiology report, the type of probable pathologies and their percentage were determined. Results: The patient's mean age was 39.78±17.43 yrs. CT scan abnormalities were reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In another study by Zarmehri et al, their study population had a mean age of 39.78 ± 17 years. 11 Additionally, this study revealed that elderly patients had more abnormal CTB findings. More vascular pathologies were seen in older patients and more infective pathologies in younger and HIV infected patients.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In another study by Zarmehri et al, their study population had a mean age of 39.78 ± 17 years. 11 Additionally, this study revealed that elderly patients had more abnormal CTB findings. More vascular pathologies were seen in older patients and more infective pathologies in younger and HIV infected patients.…”
Section: Discussionmentioning
confidence: 63%
“…A study by Zarmehri et al also consisted of more males, accounting for 62% of their study population. 11 In contrast, in a retrospective study performed in South Africa by Smith et al, their study sample consisted of more females, accounting for 61.2%. 7 Another study by Kaur et al had 65% male subjects.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation